The question says: Given y = xsinx, prove that y" + y' = 2cosx. I found that y' = sinx + xcosx, and y" = 2cosx - xsinx. But I cannot figure out how to simplify (2cosx - xsinx) + (sinx + xcosx) so that it equals 2cosx. Help? Jeannine
Follow Math Help Forum on Facebook and Google+
Hi, Originally Posted by jbecker007 The question says: Given y = xsinx, prove that y" + y' = 2cosx. I found that y' = sinx + xcosx, and y" = 2cosx - xsinx. That's correct. But I cannot figure out how to simplify (2cosx - xsinx) + (sinx + xcosx) so that it equals 2cosx. I think the question should be "Given , prove that ".
View Tag Cloud